The looming threat of EVALI in India: addressing the rise of vaping: associated lung injury - Kuthe, Swarali M.; Kokane, Noopur; Khatri, Sachin; Rewatkar, Komal; Alok, Abhinav; Datarkar, Shrinesh A. (International Journal Of Community Medicine And Public Health, 2025)
Vaping is currently banned in India, yet documents reveal a concerning prevalence of vaping across the country. This paradox calls for immediate attention, as the dangers associated with vaping are not hypothetical but have already caused a significant health crisis globally. The EVALI (e-cigarette or vaping-associated lung injury) epidemic in the United States serves as a stark warning. In the U.S., this epidemic overwhelmed healthcare systems, leading to thousands of hospitalizations and even deaths. If such a situation were to occur in India, the consequences would be disastrous. India’s healthcare system, though robust in many aspects, is not prepared to handle an outbreak of vaping-related health crises. With vaping being banned, healthcare workers may lack the necessary training and resources to effectively address the health complications associated with it. The situation could spiral out of control, straining healthcare infrastructure and putting lives at risk. Therefore, it is imperative that stricter enforcement of the vaping ban is implemented, accompanied by heightened awareness campaigns for both healthcare professionals and the general public. Preventive measures, including education on the dangers of vaping and the enforcement of the law, are essential to safeguard public health and prevent a potential public health disaster in India.